2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32118
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Students’ Prior Knowledge and Learning in an Engineering Management Course for Civil Engineers

Abstract: His academic experience includes: transportation infrastructure planning and design, infrastructure resilience, traffic operations, highway safety, and geographic information systems. His research interests include: constructing spatial databases for better management of transportation infrastructure, improving transportation design, operation, safety and construction, understanding long-term effects of urban development patterns, and advancing active living within the built environment for improved public hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The highest mean to stimulate learning of technical skills was that the TVET students believed (M=4.13, SD=0.78) that their previous knowledge is essential for technical learning in item 19. The result of the present study is similar to the result of Ghanat and Davis (2019) which revealed that the student's prior engineering management knowledge helped their understanding of engineering management topics at the Citadel. The second highest mean revealed that the TVET students agreed (M=4.10, SD=0.83) that the digital mind map can be used in various creative ways, and it can enhance their learning of technical skills (item 24).…”
Section: Tvet Student's Perceptions On the Digital Mind Map To Stimul...supporting
confidence: 85%
“…The highest mean to stimulate learning of technical skills was that the TVET students believed (M=4.13, SD=0.78) that their previous knowledge is essential for technical learning in item 19. The result of the present study is similar to the result of Ghanat and Davis (2019) which revealed that the student's prior engineering management knowledge helped their understanding of engineering management topics at the Citadel. The second highest mean revealed that the TVET students agreed (M=4.10, SD=0.83) that the digital mind map can be used in various creative ways, and it can enhance their learning of technical skills (item 24).…”
Section: Tvet Student's Perceptions On the Digital Mind Map To Stimul...supporting
confidence: 85%
“…Students who have to play catch-up may become disenchanted with their engineering degree program [6]. Past research used both qualitative and quantitative approaches to demonstrate positive correlations between prerequisite knowledge and performance in subsequent courses [7][8][9][10][11][12][13]. The observed positive correlations indicate progressive knowledge development from course to course, which is reflected in the engineering curriculum in the form of prerequisites [14].…”
Section: Introductionmentioning
confidence: 99%